Women Wavemakers : Practical Strategies for Recruiting and Retaining Women in Coding Bootcamps - World Bank Group (World Bank, Washington, DC, 2018)
Coding bootcamps have recently emerged as a promising approach to equipping individuals with the skills needed to thrive in digital economies. But despite the potential of these training programs to prepare graduates to compete in a changing global labor market, women often participate at significantly lower rates. When women do enroll, they tend to have higher dropout rates than men. The insights in this report draw on interviews with 25 coding bootcamps and 7 digital skills programs in 22 countries. The goal is to share insights and strategies from practitioners around the world on ways to recruit and retain women in coding bootcamps. The report also discusses approaches to making labor market linkages with the larger objective of tackling the underrepresentation of women in technology.